Religion-Based Character Education Management: A Co-optation Approach in Education - Umi Salamah; Punaji Setyosari; Yusuf Hanafi; Oktaviani Adhi Suciptaningsih; Zahara Hussin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Character education tended to be co-opted by religious values through numerous conceptual and practical approaches. This study underscored the co-optation of religion in the character education process as applied at an Islamic boarding school. The didactic stages were trapped to articulate religious-based character only; thus, the complex meanings of character were narrowed by overlooking other potential principles. Data were collected through observation, interviews, and documentation using the institution’s curriculum design. The findings indicated that leaders and teachers had a significant role in co-opting religious values for conceptualizing the schooling program. This was revealed in the curriculum content encompassing dominant spiritual standards. Equally, students' understanding of character appeared to be constructed by devout teachings. A slight character interpretation was exposed by religious perspectives co-opted by leaders, teachers, and curriculum. Therefore, the slender construal of character was disposed disregarding further principles having valuable points. This study recommended the need for stakeholder consideration, especially educational institutions, and Islamic boarding schools, for accommodating other values in shaping the pupils’ character, thus they were capable to compete with increasingly constricted global changes dynamically.